Optimization of Drilling Parameters on EN31 Steel with Chromium Coated Drill Bit by Using TAGUCHI Method - Balakumaran, V.; Parthasarathy, C.; Chandradass, J. (Asian Review of Mechanical Engineering, 2015)
The metal cutting is very essential to try for high metal removing rate and the best product quality. The major problem in achieving high productivity and best quality is short life span of a tool. To enhance the life of tool many new materials are developed so has to meet the market demand and competitive price for this there should be proper control over various cost involved in machining named as material cost labor cost and tooling cost the material cost can be controlled by using special material which meet all required properties with reduced price. The methodology of Modified Taguchi optimization method for simultaneous minimization and maximization of Surface roughness (Ra), machining time and material removal rate of EN31 Alloy steel affect the aesthetical aspect of the final product and hence it is essential to select the best combination values of the CNC drilling process parameters to minimize as well as maximize the responses. The experiments were carried out by a CNC lathe, using physical vapor deposition coated Chromium nitride drilling tool bit for the machining of EN19. The experiments were carried out as per L9 orthogonal array with each experiment performed under different conditions of such as speed, type of drilling tool, and feed rate. The Taugchi method and analysis of variance (ANOVA) was employed by using MINITAB-15 software to identify the level of importance of the machining parameters on Surface roughness (Ra), Machining time and Material Removal Rate (MRR).